Interleukin-23 receptor expressing γδT cells locally promote early atherosclerotic lesion formation and plaque necrosis in mice - Gil-Pulido, Jesus; Amezaga, Nuria; Jorgacevic, Ivana; Manthey, Helga D.; Roesch, Melanie; Brand, Theresa; Cidlinsky, Peter; Schafer, Sarah; Beilhack, Andreas; Saliba, Antoine-Emmanuel; Lorenz, Kristina; Boon, Louis; et al. (Cardiovascular Research, 2022)
Aims: Atherosclerosis is a chronic inflammatory disease of the vessel wall controlled by local and systemic immune responses. The role of interleukin-23 receptor (IL-23R), expressed in adaptive immune cells (mainly T-helper 17 cells) and γδT cells, in atherosclerosis is only incompletely understood. Here, we investigated the vascular cell types expressing IL-23R and addressed the function of IL-23R and γδT cells in atherosclerosis. Methods and results: IL-23R+ cells were frequently found in the aortic root in contrast to the aorta in low-density lipoprotein receptor deficient IL-23R reporter mice (Ldlr-/-Il23rgfp/+), and mostly identified as γδT cells that express IL-17 and GM-CSF. scRNA-seq confirmed γδT cells as the main cell type expressing Il23r and Il17a in the aorta. Ldlr-/-Il23rgfp/gfp mice deficient in IL-23R showed a loss of IL-23R+ cells in the vasculature, and had reduced atherosclerotic lesion formation in the aortic root compared to Ldlr-/- controls after 6 weeks of high-fat diet feeding. In contrast, Ldlr-/-Tcrδ-/- mice lacking all γδT cells displayed unaltered early atherosclerotic lesion formation compared to Ldlr-/- mice. In both HFD-fed Ldlr-/-Il23rgfp/gfp and Ldlr-/-Tcrδ-/- mice a reduction in the plaque necrotic core area was noted as well as an expansion of splenic regulatory T cells. In vitro, exposure of bone marrow-derived macrophages to both IL-17A and GM-CSF induced cell necrosis, and necroptotic RIP3K and MLKL expression, as well as inflammatory mediators. Conclusions: IL-23R+ γδT cells are predominantly found in the aortic root rather than the aorta and promote early atherosclerotic lesion formation, plaque necrosis, and inflammation at this site. Targeting IL-23R may thus be explored as a therapeutic approach to mitigate atherosclerotic lesion development.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Atherosclerosis; Inflammation; Lymphocyte; T cells